“Imagine this smart speaker to have a body”: An analysis of the external appearances and the characteristics that people associate with voice assistants - Carolus, Astrid; Wienrich, Carolin (Frontiers in Computer Science, 2022)
Modern digital devices such as conversational agents simulate human-human interaction to an increasing extent. However, their outward appearance remains distinctly technological. While research revealed that mental representations of technology shape users’ expectations and experiences, research on technology sending ambiguous cues is rare. To bridge this gap, this study analyzes drawings of the outward appearance participants associate with voice assistants (Amazon Echo or Google Home). Human beings and (humanoid) robots were the most frequent associations, which were rated to be rather trustworthy, conscientious, agreeable and intelligent. Drawings of Echos and Google Homes differed marginally but ‘human’, ‘robotic’ and ‘other’ associations differed regarding, e.g., ascribed humanness, consciousness, intellect, affinity to technology and innovation ability. This study aims to further elaborate on the rather unconscious cognitive and emotional processes elicited by technology and discusses the implications of this perspective for developers, users and researchers